Qualitative assessment of transcultural psychotherapy by adolescents and their migrant families: Subjective experience and perceived effectiveness. - Emilie Carretier; Léa Grau; Malika Mansouri; Marie Rose Moro; Jonathan Lachal (PLoS ONE, 2020)
Objective Adolescent migrants present psychological disorders more frequently than the corresponding host population but their access to care and to follow-up are less effective. The French method of transcultural psychotherapy (TPT) was conceived to respond to these problems. Our objective is to assess how these adolescents and their families perceive the experience and effectiveness of TPT. Method We conducted semistructured interviews with the families of adolescents seen for TPT. The data were analyzed by a qualitative thematic methodology. Results We spoke to 21 participants in 8 families. The families came to TPT with a sense that the teen's current treatment was at an impasse. During the follow-up, they noted that family communication and relationships had improved, as had their connection to their culture of origin. Besides commenting on what they perceived as limitations, families identified specific elements of TPT as therapeutic. Conclusion The pronounced diversity of the group and the use of both multiperspective narration and an interpreter were specific elements driving the construction of a good therapeutic alliance, despite the initial barriers. Pursuit of the evaluation of TPT is essential to advance the psychiatric care of adolescent migrants.